Cardiometabolic treatment decisions in patients with type 2 diabetes: the role of repeated measurements and medication burden. Issue 5 (27th April 2010) - Voorham, J; Haaijer-Ruskamp, F M; Wolffenbuttel, B H R; Stolk, R P; Denig, P
Abstract : Purpose: Clinical guidelines for cardiometabolic risk management indicate a simple threshold-based strategy for treatment, but physicians and their patients may be reluctant to modify drug treatment after a single elevated measurement. We determined how repeated measurements of blood pressure, cholesterol and haemoglobin A1c affect general practitioners' decisions to start or intensify medication in patients with type 2 diabetes. We also evaluated whether medication burden altered these decisions. Methods: We conducted a cohort study in 3029 patients managed by 62 general practitioners (GPs). We assessed the predictive value of the last risk factor measurement, the number of successive measurements above target level and the percentage change between the last two measurements. Medication burden was assessed as the number of drugs concurrently used. Effects on treatment decisions were estimated by multilevel logistic regression analysis, correcting for clustering at GP level. Results: Repeated high levels of diastolic blood pressure increased the likelihood to start antihypertensive medication (OR=2.08, CI 1.37 to 3.17). Repeated high haemoglobin A1c levels affected intensification of oral glucose-lowering medication (OR=1.71, CI 1.44 to 2.03). Modification of lipid-lowering medication was limited, and only affected by the last total cholesterol level. Starting treatment for all three risk factors, as well as intensifying antihypertensive treatment, was more likely in patients already using more drugs for other chronic diseases. Conclusions: Waiting for the next measurement before deciding to change medication can explain in part the apparent undertreatment for hypertension and hyperglycaemia, but not for hypercholesterolaemia. Medication burden was not a barrier for treatment modification.